Odd number : a reflective essay, on the filmmaker, Marius van Straaten's practice in Odd Number a documentary about Rashaad Adendorf, with a focus on representation - Van Straaten, Marius (Centre for Film and Media Studies, 2015)
This paper is a reflective essay supporting the documentary film Odd Number and aims to clarify and create more depth for the reader around the film's successes and failures in representing Rashaad Adendorf. Rashaad was formerly an assassin for a feared gang but is now a redeemed family man. His life is explored through interviews with him, his victims, his family and his enemies. Re-enactments of his most significant life changing events are used to inform the audience. A film representing Rashaad's life inevitably raises questions around representation and the filmmaker's relationship with Rashaad. The essay concludes that a weakness of Odd Number is its lack of self-reflexivity and lack of showing the filmmaker's process and bias. The paper identifies that the key strength of the film is the relationship and friendship between Rashaad and the filmmaker and how that influences the process of making the film. The paper concludes that through Odd Number, Rashaad has claimed agency, not only to rebuild or redeem his own life, but to work to improve the lot of the community. The paper argues that this is the best possible legacy Odd Number could leave. The film and reflective essay demonstrate that the relationship with the subject is of primary importance and that focussing on the process rather than the outcome can result in a more honest, albeit subjective portrayal of a subject from a different race, class and background to the filmmaker. Ideally the paper should be read after having watched, the documentary Odd Number. It is important to note that the author of this paper is also the director of Odd Number. This paper is therefore not an analysis of somebody else's work, but a set of reflections by the director on his own work. The paper therefore communicates in the first person, aswell as the third person from time to time.